Investigating human motor learning using multimodal imaging and brain stimulation - Hinson, E (2019)
Many post-stroke motor rehabilitation programmes are developed from methods used to augment and improve motor skill learning in healthy controls. An important step towards developing effective motor rehabilitation strategies is therefore understanding the neurophysiology of healthy motor learning, and then assessing if (and if so, how) this changes after a stroke.